Analysis and explanation sprawl in industrial cities (Case study: Bandar Mahshahr) - arash ghasemphour; azadeh arbabi; naser ebadati; fatemeh adibi; maryam rostam pishe (تحقیقات کاربردی علوم جغرافیایی)
This research has been carried out with the aim of analyzing and explaining the spatial distribution of Mahshahr port during the years (1981-2021). The research method is descriptive-analytical and practical in terms of targeting. For data analysis, cross-tab, kappa coefficient, sectorial, Heldren and Markov chain models were used. In this regard, Envi 5.3, Terrset, Arc/Gis and Google Map software were used to analyze the obtained information. The geographical scope of this research is the city of Mahshahr according to the census of 2015. Kappa coefficient of Mahshahr port spatial changes map for  1981, 2001 and 2021 is equal to 0.88, 0.94 and 0.94 respectively. The results of this research show that during the years 2001 to 2021, about %75 of the growth of Mahshahr city is related to population increase and %25 is related to horizontal and physical growth. The spreading pattern of Mahshahr port is expanding in the form of clusters in the north, north-west, west and south-west directions. According to the forecast results for the time horizon of 2041, the growth of Mahshahr port will reach from 1657 hectares in 2021 to 2530 hectares in 2041. If there is no optimal management, the dispersal of Mahshahr port and its agricultural lands will undergo many changes in the not-so-distant future, and this will have adverse effects on the residents of this city due to the climatic condition of the city and global warming.